Banal Nationalism 20 years on: Re-thinking, re-formulating and re-contextualizing the concept. (September 2016) - Koch, Natalie; Paasi, Anssi
Abstract: This introduction considers the significance of Michael Billig's (1995) Banal Nationalism to geographers, and how this fits into broader trends of nationalism research in the social sciences. Through an analysis of Web of Science citation trends for the book, we illustrate its spatial and temporal reach in terms of the countries where it has been cited and how its impact has developed since 1995. We also briefly examine how political geographers have engaged the concept of banal nationalism in their research, and what sort of questions it has raised for those conducting research on nationalist discourses and territorial identity narratives more broadly. Considering how political geographers might creatively advance this scholarship, we introduce the individual papers included in this special issue and conclude with a brief gesture to future directions for research beyond Banal Nationalism.